(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2026)
The present research explores the symbolism of nature in Emily Dickinson’s poetry with particular attention to the poetic function of natural imagery. The study argues that Dickinson uses nature not merely as a background or decorative element, but as a symbolic system through which she conveys existential, spiritual, and emotional concerns. Through qualitative textual analysis of selected poems, the research demonstrates how symbols such as birds, seasons, flowers, light, and natural landscapes reflect inner psychological states and philosophical reflections. The findings show that nature imagery plays a crucial role in shaping the meaning and originality of Dickinson’s poetry.